Gusti Yesus Rawuh Paring Urip Lan Kaluberan: (Pengabdian Melalui Pembinaan Iman Dalam Rangka Paskah di G.Pibi Amanat Agung, Pos Pelayanan Mojo Gedang, Karang Anyar, Jawa Tengah) - Epafras Mujono; Ruth Melisa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The background to this Community Service Activity (PkM) is: First, there is a need among congregation members for speakers/lecturers/who can speak Javanese so that the participants better understand the material for faith formation, in the context of commemorating Good Friday and Easter. Second, there is a need to refresh the commitment of congregation members in their faith in Jesus Christ. Third, there is a need for a correct understanding of Good Friday and Easter for the general public, so that they get the correct information about this. The aim of this Community Service activity is as follows: First, so that the message of the lecture about the coming of Jesus who gives life and abundance (John 10:10b) can be captured or understood more clearly by the recipients of this PkM service, because it is delivered in Javanese . Second, to explain the material for community service through faith formation lectures. Third, to determine respondents' satisfaction as participants in this community service activity. The results of this devotion are: First, faith formation material with the theme